Analysis of Herbal Drugs by HPTLC: A REVIEW - B, Gunjal Sanket; R, Dighe P. (Asian Journal of Pharmaceutical Research and Development, 2022)
Densitometric evaluation through HPTLC is very useful method for standardization of medicinal plants and other natural products, especially those used in different system of medicine. It has been approved as an authenticated method of analysis in several pharmacopeias, including the USP and the IP. Result from a number of medicinal plants studied in the laboratory have shown that, TLC- densitometry is more advantageous strategy than HPLC or GLC. Improvement in resolution, HPTLC is valuable tool for the investigation of herbal products with respect to different aspects of their quality. sensitivity and reproducibility are the fundamental attributes. HPTLC plays an important role in the characterization of marker compounds for the development and standardization of herbal medicines. The HPTLC approach is particularly well suited to the examination of herbs and herbal preparations because it allows for easy comparison of samples using fingerprints and quantitative determination using scanning densitometry. Herbs and herbal mixtures are particularly challenging to standardise. Many of the current medications we use today for various ailments are based on plants and plant-based products. This review focused on the various HPTLC methods used to analyse herbal drugs. For each drug, extraction processes as well as the HPTLC analytical method have been optimised.